2013
DOI: 10.9734/bmrj/2013/2511
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Microbiological Level and the Incidence of Water-soaking on the Proximate Composition of two Cultivars of Cowpea (Vigna unguiculata L.) Grains Grown in Côte d’Ivoire

Abstract: This work was carried out in collaboration between all authors. Author RKN designed the study, performed the statistical analysis, wrote the protocol, and wrote the first draft of the manuscript. Author MK managed the analyses of the study. Author KK performed the analysis in the laboratories and managed the literature searches. Author WAMAB managed the analyses of the study and revised the first draft. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The domination of Aspergillus spp is of food safety prime importance because, they are highly toxigenic. The isolation of mycotoxigenic fungi and the predominance of the genus Aspergillus in food agree with the work done by [17] and [18]. The genus Penicillium was also isolated with 22.2% of the samples contaminated.…”
Section: Resultssupporting
confidence: 88%
“…The domination of Aspergillus spp is of food safety prime importance because, they are highly toxigenic. The isolation of mycotoxigenic fungi and the predominance of the genus Aspergillus in food agree with the work done by [17] and [18]. The genus Penicillium was also isolated with 22.2% of the samples contaminated.…”
Section: Resultssupporting
confidence: 88%
“…This current study showed a relatively higher ash content in all the formulated samples than previously reported by Adisetu et al [43] who also worked with OFSP complementary foods. The inconsistency in the ash content across OFSP complimentary foods studies may be attributed to differences in maceration and dehulling time which have strong implications for the minerals' solubility [3].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported to preserve the health benefits and enhances the nutritive values of complementary food products [2]. Koffi-Nevry et al [3] reported that soaking induces antinutritional losses through diffusion. Thus, soaking represents a technological process for the removal of soluble compounds and may attract application as an alternative to decrease the antinutritional contents of foods [4].…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the third largest producer of corn with 84 million tons of corn grain produced in the 2014/15 growing season (CONAB 2016). However, the sanitary quality of grains creates barriers to export and poses serious risks to human health (Koffi-Nevry et al 2013). In recent years, there is a growing public and private demand for high quality and safe grains for food and feed.…”
mentioning
confidence: 99%